Dual Vinorelbine bitartrate and Resveratrol loaded polymeric aqueous core nanocapsules for synergistic efficacy in breast cancer - Lakshmi; Singh S.; Shah K.; Dewangan H.K. (My University, 2025)
Aim: The current study focussed on the development and evaluation of aqueous core nanocapsules (ACNs) as an effective carrier to deliver an optimal synergistic combination of a highly water-soluble Vinorelbine bitartrate (VRL) and a poorly water-soluble Resveratrol (RES) for treatment of breast cancer. Methods: Various molar ratios of VRL to RES were screened against MCF-7 cell lines to determine the synergistic effects using the Chou-Talalay method. The synergistic ratio of therapeutic agents was then incorporated into aqueous core nanocapsules utilising a double emulsion solvent evaporation technique to yield dual drug-loaded nanocapsules (dd-ACNs). The dd-ACNs were optimised using Box-Behnken design and characterised for physicochemical parameters such as particle size, zeta potential, polydispersity index, total drug content and encapsulation efficiency, surface morphology, drug excipient compatibility by FTIR and DSC, release kinetics, toxicity studies and anticancer efficacy (in-vitro and in-vivo). Results: Results demonstrated that the combination exhibited maximum synergy when higher doses of VRL were combined with smaller doses of RES (1:1, 5:1, and 10:1). The dual drug-loaded ACNs were found to be stable and depicted a core-shell structure, narrow size range (150.2 ± 3.2 nm) with enhanced encapsulation (80% for VRL and 99% for RES). Moreover, the dd-ACNs were 5 times more efficacious in-vitro than a combination of free drugs, while reducing systemic toxicity. Also, pre-clinical evaluation of dd-ACNs also depicted a drastic reduction of tumour volume as compared tp pristine VRL and a physical combination of drugs. Conclusion: The developed dd-ACNs can be applied as a potential carrier for delivery of a combination of chemotherapeutics at a synergistic ratio at the tumour site. © 2022 Informa UK Limited, trading as Taylor & Francis Group.